Family Secrets - Byrski, Liz (Pan Macmillan, 2014)
When patriarch Gerald Hawkins passes away in his Tasmanian home after ten years of serious illness, his family experiences a wave of grief and, admittedly, a surge of relief. Gerald's dominating personality has loomed large over his wife Connie and their children, Andrew and Kerry, for most of their lives. Connie, whose own dreams were dispensed with upon marriage, is now determined to renew her long friendship with Gerald's estranged sister. She travels to France where she finds Flora struggling to make peace with the past and searching for a place to call home. Meanwhile Andrew's marriage is crumbling, and Kerry is trapped in stasis by unfinished business with her father. As the family adjusts to life after Gerald, they could not be more splintered. And there are surprises in store and secrets to unravel that could either unite or divide them forever. Is it possible that they could find a way to start afresh with forgiveness, understanding and possibility? Or is Gerald's legacy too heavy a burden to overcome?